Superior performance through digitalization in the meal delivery industry : a closer look on smart speakers - Gierlach, Kevin (2018)
This thesis strives to give insights whether digitalization in the meal delivery with a focus on smart speakers can lead to superior performance. One finding is that an increased access to smart speakers has a positive effect on the number of meals ordered at home. It further finds that an increased ability of smart speakers to understand voice input could accelerate sales of smart speakers significantly. The main finding of this work is that the digitalization within the meal delivery industry with a focus on smart speakers does lead to superior performance. Since the topic is very recent this work gives the reader a framework to understand the functionality of smart speakers and the underlying technologies such Natural Language Processing which is based on artificial intelligence. Moreover, different digital business models within the meal delivery industry are introduced to give the reader an overview on the market, recent developments, and the market potential. The market research found that restaurants focusing on digitalizing can indeed achieve significant superior performance.